Discovery of young submarine volcanism in the Cook Islands: New constraints on the location of the Rarotonga hotspot - Yifan Du; Matthew G. Jackson; Brian Jicha; Andrew Kylander-Clark; Benjamin L. Byerly; Michael Bizimis; Sæmundur Ari Halldórsson; Gareth G.E. Seward; Olivia E. Anderson; Matthew Rioux; Kevin Konrad; Sunna Harðardóttir; et al. (Geochimica et Cosmochimica Acta, 2026)

Phytophagous insect community assembly through niche conservatism on oceanic islands - David H. Hembry; Tomoko Okamoto; Gerald McCormack; Rosemary G. Gillespie (Journal of Biogeography, 2013)
Aim To determine whether a community of phytophagous insects on oceanic islands (the fauna of insects feeding internally on G lochidion trees in south‐eastern P olynesia) was assembled predominantly through niche conservatism or adaptive radiation. Location The islands of south‐eastern P olynesia (southern C ook, A ustral, S ociety, T uamotu‐ G ambier and M arquesas archipelagos) in the C ook I slands and F rench P olynesia. Methods Internally feeding insects were collected as larvae from 23 endemic species of G lochidion ( E uphorbiaceae s.l., P hyllanthaceae: P hyllanthus s.l.) trees on 20 islands in south‐eastern P olynesia, reared and identified. Rearing records were compared with host records previously known from the literature and museum collections of closely related taxa in A sia and A ustralasia. Results Ninety per cent of insect specimens collected fall into five taxa previously known to attack G lochidion in A sia and A ustralasia (≥ 6000 km distant), indicating a strong role for niche conservatism in the assembly of this community. Three of these taxa, two seed‐feeding moths ( G racillariidae: E picephala ; T ortricidae: T ritopterna ) and a leaf‐mining moth ( G racillariidae: D iphtheroptila ) are only known from Phyllanthaceae or Euphorbiaceae s.l. on continents. Two more taxa, another leaf‐mining moth ( G racillariidae: C aloptilia ) and a leaf‐rolling moth ( T ortricidae: D udua ), contain many species known only from P hyllanthaceae on continents, and are also very likely to represent examples of niche conservatism. Conversely, many numerically dominant insect taxa known from G lochidion on continents (such as parasitoid H ymenoptera) are not reported from south‐eastern P olynesia. This indicates that the insular community represents a subset of those taxa from the continental community, consistent with the well‐established P acific diversity gradient. Main conclusions These findings indicate that niche conservatism can play an important role in the assembly of phytophagous insect communities on oceanic islands, despite the constraints that specialization might be expected to pose on successful establishment. As a result of this niche conservatism, these communities may represent less species‐rich versions of continental tropical communities rather than non‐analogue insular ecosystems.